2003
DOI: 10.1007/s00442-002-1093-3
|View full text |Cite
|
Sign up to set email alerts
|

Adult beetle grazing induces willow trichome defence against subsequent larval feeding

Abstract: Induced increases in trichome density to grazing by herbivores have been suggested to increase plant resistance to future herbivore attack. In this paper we present results which show that plants of Salix cinerea L. respond to adult leaf beetle (Phratora vulgatissima L.) grazing by developing new leaves with an increased trichome density. The same plants are usually attacked again later in the season when the next generation of larvae hatches on the plants. The effect of the induced response was studied by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 34 publications
3
73
0
1
Order By: Relevance
“…This independence of morphological and physiological features has been documented in other plant species (Roy et al, 1999;Forkner & Hare, 2000). However, increased trichome density may be induced by heavy herbivore defoliation or by intense disturbance events, such as hurricanes (Pullin & Gilbert, 1989;Dalin & Bjo¨rkman, 2003;Spiller & Agrawal, 2003) -this alternative has not been tested in the present system.…”
Section: Discussionmentioning
confidence: 99%
“…This independence of morphological and physiological features has been documented in other plant species (Roy et al, 1999;Forkner & Hare, 2000). However, increased trichome density may be induced by heavy herbivore defoliation or by intense disturbance events, such as hurricanes (Pullin & Gilbert, 1989;Dalin & Bjo¨rkman, 2003;Spiller & Agrawal, 2003) -this alternative has not been tested in the present system.…”
Section: Discussionmentioning
confidence: 99%
“…22 This increase in trichome density in response to damage can only be observed in leaves developing during or subsequent to insect attack, since the density of trichomes of existing leaves does not change. 16 Dalin and Bjorkman 23 reported that damage by adult leaf beetles, Phratora vulgatissima L. in Salix cinerea L. induced higher trichome density in the new leaves developing thereafter. Likewise, increase in trichome density in S. cinera in response to coleopteran damage has also been reported.…”
Section: Mechanisms Of Plant Defense Against Insect Herbivoresmentioning
confidence: 99%
“…Changes in trichome density occur within days or weeks after insect damage. [22][23][24] Furthermore, change in relative proportion of glandular and non-glandular trichomes is also induced by herbivory. 22 A positive correlation has been observed between natural enemies' abundance and trichome density.…”
Section: Mechanisms Of Plant Defense Against Insect Herbivoresmentioning
confidence: 99%
“…3,4,5 Acclimation occurs both on the biochemical and morphological level, e.g., by increasing defence compounds, 6 by synthesizing defence related proteins, by emitting volatiles to attract predators and parasites of herbivores 7 and by altering plant morphology via increased formation of trichomes, thorns or scleromorphy. 8,9 Many studies demonstrated resource based trade-offs between growth and defence on a large time scale (e.g. refs.…”
mentioning
confidence: 99%